Evaluasi Keamanan Makanan Jajanan Cilok Bakso Ditinjau dari Kandungan Boraks dan Formalin di Beberapa Sekolah Menengah Pertama (SMP) Wilayah Kabupaten Sukoharjo - Dwi Cahyo Nugroho; Agustina Intan Niken Tari; Catur Budi Handayani (Universitas Veteran Bangun Nusantara, 2023)
This study aims to determine the presence of borax and formalin in snacks for junior high school children in Sukoharjo Regency, namely cilok and meatballs. The method used in this study uses a qualitative purposive method. This research consists of 2 stages. First, sampling and determination of the sample was carried out using a stratified survey method with 3 levels, the first level was to determine the sub-district, the second level was to determine the number of junior high schools and the third level was to determine the sample of cilok and meatballs. Sampling was determined in 6 selected sub-districts from the 12 sub-districts, 4 junior high schools were selected. There were 24 samples of snacks, consisting of 13 samples of cilok and 11 samples of meatballs. The results showed that there was no borax in the meatball or cilok samples. There were 9 out of 13 samples of cilok indicated containing formalin, while in meatballs there were 7 out of 11 samples indicated containing formalin. The second stage is testing samples with laboratory tests using turmeric extract for the borax test and KMnO4 for the formalin test. The conclusion of this study, there are still some meatball and cilok traders using hazardous materials such as formalin to preserve their wares.